Artificial Rod and Cone Photoreceptors with Human‐Like Spectral Sensitivities. Issue 27 (18th May 2018) - Park, Byeongho; Yang, Heehong; Ha, Tai Hwan; Park, Hyun Seo; Oh, Seung Ja; Ryu, Yong‐Sang; Cho, Youngho; Kim, Hyo‐Suk; Oh, Juyeong; Lee, Dong Kyu; Kim, Chulki; Lee, Taikjin; et al.
Abstract: Photosensitive materials contain biologically engineered elements and are constructed using delicate techniques, with special attention devoted to efficiency, stability, and biocompatibility. However, to date, no photosensitive material has been developed to replace damaged visual‐systems to detect light and transmit the signal to a neuron in the human body. In the current study, artificial nanovesicle‐based photosensitive materials are observed to possess the characteristics of photoreceptors similar to the human eye. The materials exhibit considerably effective spectral characteristics according to each pigment. Four photoreceptors originating from the human eye with color‐distinguishability are produced in human embryonic kidney (HEK)‐293 cells and partially purified in the form of nanovesicles. Under various wavelengths of visible light, electrochemical measurements are performed to analyze the physiological behavior and kinetics of the photoreceptors, with graphene, performing as an electrode, playing an important role in the lipid bilayer deposition and oxygen reduction processes. Four nanovesicles with different photoreceptors, namely, rhodopsin (Rho), short‐, medium‐, and longwave sensitive opsin 1 (1SW, 1MW, 1LW), show remarkable color‐dependent characteristics, consistent with those of natural human retina. With four different light‐emitting diodes for functional verification, the photoreceptors embedded in nanovesicles show remarkably specific color sensitivity. This study demonstrates the potential applications of light‐activated platforms in biological optoelectronic industries. Abstract : Artificially synthesized biological nanomaterials with four types of photoreceptors in nanovesicles show outstanding spectral characteristics, similar to those of the human eye for visible light, on a graphene working electrode for electrochemical measurement.